Lightweight wear-resistant composite fiber and preparation method thereof
By modifying the combination of wool fiber, polyester fiber, silver-plated acrylic fiber and yeast protein adhesive, lightweight and wear-resistant composite fibers are prepared by using jet vortex blending technology, which solves the wear resistance index and average line density of existing composite fibers. and mechanical properties have achieved higher wear resistance, flexibility and anti-static properties.
Patent Information
- Application Number
- CN202411933139.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing composite fibers need to be further improved in terms of wear resistance index, average line density and mechanical properties, and there are problems of static electricity and thickness.
Lightweight and wear-resistant composite fibers are prepared by jet vortex blending technology using a combination of modified wool fibers, polyester fibers, silver-plated acrylic fibers and yeast protein adhesives. Modified wool fibers are catalyzed by thermophilic mycelial laccase to form oligomers, enhancing their mechanical properties and wear resistance index; polyester fibers are prepared by copolymerization, with softness and low density; silver-plated acrylic fibers are coupled by silane The agent and silver ammonia solution can improve the wear resistance index and antistatic properties; the yeast protein adhesive improves adhesion and wear resistance through the cross-linking reaction of ammonized waste paper fibers and yeast protein.
It significantly improves the wear resistance index, mechanical properties and antistatic properties of composite fibers, reduces the average line density and resistivity, and improves the wearing experience.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite fiber processing, and in particular to a lightweight and wear-resistant composite fiber and a preparation method thereof. Background Art
[0002] The fabric wear resistance index refers to the performance of the fabric in resisting wear. Wear refers to the phenomenon that the fabric is gradually damaged by repeated friction from other objects during use. At present, people have successfully developed many fabrics with excellent wear resistance by using some surface modification methods.
[0003] Wool fiber is a natural protein fiber with many excellent properties. It not only has a plump feel, but also has excellent comfort and warmth retention. These excellent properties make wool fabrics deeply loved by consumers.
[0004] Although wool fibers have excellent properties of comfort and warmth retention, their surface is covered with a loosely arranged keratin scale layer structure. This structure causes wool fibers to often wear due to external friction in actual applications, which reduces the wear resistance index of wool fibers. In addition, the average linear density of wool fibers is too large, which makes them thicker than ordinary polyester fiber clothes when used in clothing. In cold and dry conditions, the surface of wool fibers carries negative charges due to frictional charging, causing skin discomfort to the wearer.
[0005] In the prior art, nanomaterials are often coated on the surface of wool fibers to form a nano protective film to reduce the damage of friction to the keratin scale layer structure of the wool fibers and improve the wear resistance index of the wool fibers. Although this method has a certain effect, it will make the surface of the wool fibers harder or rigid, lose their natural softness and comfort, and reduce the wearing experience. In addition, with simple physical coating, the coating may fall off or wear out as the number of uses increases. The durability of the nano coating cannot meet the needs of long-term use, and the problem that wool fibers are prone to static electricity and are relatively thick has not been well solved. Summary of the invention
[0006] The object of the present invention is to provide a lightweight and wear-resistant composite fiber and a preparation method thereof, so as to solve the technical problem in the prior art that the wear resistance index, average linear density and mechanical properties of the composite fiber need to be further improved.
[0007] The object of the present invention can be achieved by the following technical scheme: a light and wear-resistant composite fiber, which comprises, by weight: 70-75 parts of modified wool fiber, 10-12 parts of polyester fiber, 1-6 parts of silver-plated acrylic fiber and 10-18 parts of yeast protein adhesive;
[0008] The method for preparing the modified wool fiber comprises the following steps:
[0009] A1. Place wool fiber, deionized water and sodium carbonate in a three-necked flask heated to 40-50°C, stir for 0.5-1h, wash with deionized water 1-2 times, and dry to obtain alkalized wool fiber;
[0010] A2. Place the dried alkalized wool fiber in the inner cavity of a low-temperature plasma machine, inject an oxygen channel, set the power to 100-150W at a pressure of 100-120Pa, and continue the plasma discharge treatment for 5-10min to obtain pretreated wool fiber;
[0011] The reaction principle for preparing pretreated wool fibers is as follows: under alkaline conditions, the fatty acids in the wool fibers react with sodium carbonate to form salts soluble in deionized water, which can effectively remove fat and impurities on the wool after washing and drying; in an oxygen atmosphere, the oxygen atoms and oxygen molecules in the plasma undergo an oxidation reaction with the molecules on the surface of the wool fibers, introducing hydroxyl groups, carboxyl groups and aldehyde groups, increasing the polarity of the wool fibers, and helping the subsequent oligomers composed of catechol and tea polyphenols to form covalent bonds with the wool fibers through chemical bonds, thereby increasing the wear resistance index of the wool fibers.
[0012] A3. Immerse the pretreated wool fiber in the modification solution, keep the temperature for 5-6 hours, wash with deionized water 2-3 times, and dry to obtain the modified wool fiber.
[0013] Furthermore, in step A1, the amount ratio of the wool fiber, deionized water and sodium carbonate solution is 1-5g:30-150mL:0.3-1g; in step A3, the amount ratio of the pretreated wool fiber and the modified liquid is 10-50g:100-300mL, and the modified liquid is composed of catechol, tea polyphenols, thermophilic mycelium laccase solution, deionized water and sodium acetate solution in a dosage ratio of 0.15-0.2g:0.05-0.1g:0.5-1mL:5-10mL:1-2mL, the concentration of the sodium acetate solution is 0.2-0.3mol / L, and the concentration of the thermophilic mycelium laccase solution is 50-60U / mL.
[0014] Furthermore, the preparation method of the polyester fiber is: placing terephthalic acid, ethylene glycol, a catalyst and adipic acid glutaramide in a reaction kettle heated to 230-275° C., keeping the temperature for reaction for 2-5 hours, and post-treating to obtain the polyester fiber.
[0015] Furthermore, the catalyst is composed of antimony ethylene glycol and triphenyl phosphite in a weight ratio of 0.1-1:1-5, and the weight ratio of terephthalic acid, ethylene glycol, catalyst and adipic acid glutaramide is 13-15:17-20:0.1-1:12-15.
[0016] Further, the preparation method of the silver-plated acrylic fiber comprises the following steps:
[0017] B1. Place acrylic fiber, sodium carbonate and deionized water in a three-necked flask heated to 80-90° C., seal and keep warm for 0.5-1h, wash with deionized water 1-2 times, and dry to obtain a crude acrylic fiber product;
[0018] B2, placing the crude acrylic fiber, silane coupling agent and ethanol solution in a three-necked flask, reacting at 30-40° C. for 2-3 h, washing with ethanol solution 2-3 times, and drying to obtain modified acrylic fiber;
[0019] The reaction principle for preparing the modified acrylic fiber is as follows: during the reaction process, the silane coupling agent modifies the thiol groups on the surface of the crude acrylic fiber to prepare the modified acrylic fiber.
[0020] B3. Place the modified acrylic fiber, reducing agent and silver ammonia solution in a reaction kettle heated to 40-50°C, keep the temperature for reaction for 0.5-1h, wash with deionized water 1-2 times, and dry to obtain the silver-plated acrylic fiber.
[0021] Further, in step B1, the amount ratio of the acrylic fiber, sodium carbonate and deionized water is 10-20g:1-2g:100-200mL; in step B2, the silane coupling agent is mercaptopropyl triethoxysilane, the ethanol solution is composed of ethanol and purified water in a volume ratio of 90-95:5-10, and the amount ratio of the acrylic fiber crude product, the silane coupling agent and the ethanol solution is 10-15g:0.5-2g:100-200mL; in step B3, the reducing agent is prepared from glucose, potassium sodium tartrate and anhydrous ethanol in a dosage ratio of 0.5-1g:0.4-0.8g:10-15mL, and the preparation method of the silver ammonia solution comprises: dropping 5-10% ammonia water into 20-30ml0.15-0.20mol / L silver nitrate solution until it is clear, adding 20-30 1-5 mL of ethylenediamine of mol / L is added, and then 0.6-0.7 mol / L of sodium hydroxide solution is added, the pH value of the reaction solution is adjusted to 11±0.2, and 5-10% ammonia water is continuously added dropwise until it becomes clear to obtain a silver ammonia solution, wherein the amount ratio of the modified acrylic fiber, the reducing solution and the silver ammonia solution is 10-15 g: 100-150 mL: 100-150 mL.
[0022] Furthermore, the preparation method of the yeast protein adhesive comprises the following steps:
[0023] C1. Place the waste beer yeast powder, deionized water and sodium hydroxide in a three-necked flask heated to 80-100° C., add hydrochloric acid solution to adjust the pH to 9±0.5, and perform post-treatment to obtain yeast protein isolate;
[0024] C2. Put waste paper fiber, sodium hydroxide, deionized water and epichlorohydrin in a three-necked flask, react at room temperature for 3-4 hours, wash with acetone and deionized water 1-2 times to obtain an ammoniated waste paper fiber precursor, add the ammoniated waste paper fiber precursor, N,N-dimethylformamide and ethylenediamine into the three-necked flask and stir, raise the temperature of the three-necked flask to 65-75° C., keep warm for 2-3 hours, and post-treat to obtain the ammoniated waste paper fiber;
[0025] The reaction equation for preparing ammoniated waste paper fiber is:
[0026]
[0027] The synthesis principle of aminated waste paper fiber is as follows: the amination reaction occurs in a-poly anhydrous glucose ester in the waste paper fiber. Under alkaline conditions, the oxygen atom of the hydroxymethyl group in a-poly anhydrous glucose ester acts as a nucleophilic reagent to attack the positively charged carbon atom in the epoxy group, and the chloride ion in epichlorohydrin is released as a leaving group to generate a-poly anhydrous glucose ester with a propylene oxide chain segment; then, the amino group in ethylenediamine acts as a nucleophilic reagent to attack the carbon positive atom of propylene oxide in the polymer to generate aminated waste paper fiber.
[0028] C3. Place yeast protein isolate in a three-necked flask, adjust pH to 9±0.2 with sodium hydroxide solution, add ammoniated waste paper fiber and trimethylolpropane triglycidyl ether, react at 40-50°C for 20-30 minutes to obtain yeast protein adhesive.
[0029] The reaction principle of preparing yeast protein adhesive is as follows: yeast protein isolate contains a large number of polar groups of amino, carboxyl and hydroxyl groups. Under alkaline heating conditions, it forms covalent bonds and hydrogen bonds with the hydroxyl and carboxyl groups in ammoniated waste paper fibers and trimethylolpropane triglycidyl ether to form a cross-linked network structure with an adhesive effect. When used as an adhesive for composite fibers, it tightly bonds the modified wool fibers, polyester fibers and silver-plated acrylic fibers together to increase the wear resistance index and mechanical properties of the composite materials.
[0030] Furthermore, in step C1, the dosage ratio of the waste beer yeast powder, deionized water and sodium hydroxide is 1.6-2.0 g: 20-30 mL: 0.4-0.6 g; in step C2, the dosage ratio of the waste paper fiber, sodium hydroxide, deionized water and epichlorohydrin is 6-8 g: 10-15 g: 100-150 mL: 20-30 g: 10-20 mL, and the ammoniation of the waste paper fiber precursor, N,N-dimethylformyl The dosage ratio of amine and ethylenediamine is 6-8g:100-150mL:10-20mL, and the post-treatment step comprises: washing the reaction solution with deionized water for 1-2 times, and drying to obtain ammoniated waste paper fiber; in step C3, the concentration of the sodium hydroxide solution is 7.5-8.0mol / mL, and the weight ratio of the yeast protein isolate, the ammoniated waste paper fiber and trimethylolpropane triglycidyl ether is 200-400:3-6:10-20.
[0031] Furthermore, a method for preparing a lightweight and wear-resistant composite fiber is as follows: modified wool fiber, polyester fiber, silver-plated acrylic fiber and yeast protein adhesive are uniformly mixed by jet vortex blending to obtain a composite fiber.
[0032] The present invention has the following beneficial effects:
[0033] 1. In the process of preparing a lightweight and wear-resistant composite fiber, the present invention first prepares oligomers catalyzed and oxidized by laccase. Catechol and tea polyphenols can form oligomers under the action of thermophilic mycelium laccase. These oligomers are physically adsorbed on the surface of wool fibers as their concentration increases, and covalently cross-link with the hydroxyl and amino groups of the wool fibers to fill the keratin scales on the surface, thereby enhancing the breaking strength, tensile strength and wear resistance index of the composite fibers. Polyester fibers are prepared by copolymerizing adipic acid glutaramide and ethylene terephthalate. Since adipic acid glutaramide contains more methylene flexible chain segments, after being introduced into the main chain of ethylene terephthalate macromolecules, the macromolecule chains are more likely to move, so the polyester fibers have better softness, and the polyester fibers are more durable. It is a synthetic fiber whose molecular chain is mainly composed of carbon, hydrogen and oxygen, with a lower molecular weight and density, which reduces the weight of the further prepared composite fiber, reduces the average linear density of the composite fiber, and improves its softness. The silver-plated acrylic fiber is obtained by silver-plating the acrylic fiber modified by a silane coupling agent. The modified acrylic fiber contains a thiol group. The sulfur atom of the thiol group forms a coordination bond with the silver ion through a lone pair of electrons to generate a stable silver-plated chelate, which further generates antistatic and wear-resistant silver-plated acrylic fiber, improves the wear resistance index of the composite fiber, and reduces the resistivity. The modified wool fiber, polyester fiber, silver-plated acrylic fiber and yeast protein adhesive are combined and blended to further improve the wear resistance index, mechanical properties and antistatic properties of the composite material and reduce the average linear density of the composite fiber.
[0034] 2. The modified wool fiber prepared by the present invention has a significant promoting effect on the process of lightweight and wear-resistant composite materials. The adsorption or cross-linking of catechol and tea polyphenol oxygen oligomers catalyzed by the laccase of thermophilic bacteria mycelium has a filling effect on the gaps of the wool scales of the wool fiber, which can improve the wool fiber's ability to resist repeated stress during wear. After pretreatment with sodium carbonate and plasma, the oligomers are evenly distributed on the surface of the wool fiber, further improving the mechanical properties and wear resistance index of the modified wool fiber. Silane coupling agent is added to the crude acrylic fiber to form a thiol modification on the surface. The sulfur atom of the thiol forms a coordination bond with the silver ion through the lone pair of electrons to generate a stable silver-plated chelate, and further prepares the silver-plated acrylic fiber, improves the wear resistance index of the composite fiber, and reduces the resistivity.
[0035] 3. In the process of preparing lightweight and wear-resistant composite fibers, the present invention uses ethylenediamine and epichlorohydrin to ammine and modify waste paper fibers to prepare ammoniated waste paper fibers with high reactivity. Yeast protein is used as a matrix, ammoniated waste paper fibers are used as a reinforcing phase, and trimethylolpropane triglycidyl ether is used as a cross-linking agent to prepare a yeast protein adhesive of a protein system. Trimethylolpropane triglycidyl ether and yeast protein undergo a cross-linking reaction during the preparation process to generate a macromolecular polymer, thereby increasing the molecular weight of the adhesive and increasing its viscosity. The added ammoniated waste paper fibers contain a large number of polar groups and can be connected with yeast proteins through hydrogen bonding, thereby increasing the fluid shear resistance and solid content of the protein solution and improving the adhesion of the yeast protein adhesive. Yeast protein contains abundant active groups such as amino and carboxyl groups and can undergo chemical cross-linking reactions with hydroxyl, amino and carboxyl groups on the surfaces of modified wool fibers and silver-plated acrylic fibers. These cross-linking reactions form stable covalent bonds and hydrogen bonds between the fibers, tightly bonding different types of fibers together to form a wear-resistant, lightweight and antistatic composite fiber. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The waste paper fibers used in the present invention are obtained from Lingshou County Jiaying Mineral Products Co., Ltd. The fiber length is 0.42-3 mm and the packaging specification is 10 kg / bag.
[0038] Example 1
[0039] This embodiment provides a method for preparing a lightweight and wear-resistant composite fiber, comprising the following steps:
[0040] S1. Preparation of modified wool fiber
[0041] Weigh: 0.15 g of catechol, 0.05 g of tea polyphenols, 0.5 mL of 50 U / mL thermophilic mycelium laccase solution, 5 mL of deionized water, and 1 mL of 0.2 mol / L sodium acetate solution, put them into a flask and mix them evenly to obtain a modified solution for later use;
[0042] Weigh: 1 g of wool fiber, 30 mL of deionized water and 0.3 g of sodium carbonate, put them in a three-necked flask heated to 50°C, stir for 1 hour, wash with deionized water twice, and dry to obtain alkalized wool fiber;
[0043] The dried alkalized wool fiber was placed in the inner cavity of a low-temperature plasma machine, an oxygen channel was injected, and the power was set to 150W under a pressure of 100Pa. The plasma machine continuously discharged for 5 minutes to obtain pretreated wool fiber.
[0044] Weigh: 10 g of pretreated wool fiber, immerse it in 100 mL of the modification solution, keep warm for 5 hours, wash it with deionized water for 3 times, and dry it to obtain the modified wool fiber.
[0045] S2. Preparation of polyester fiber
[0046] Weigh: 0.1 g of ethylene glycol antimony and 1 g of triphenyl phosphite, put them into a beaker and mix them evenly to obtain a catalyst for later use;
[0047] Weigh: 13g of terephthalic acid, 17g of ethylene glycol, 0.1g of catalyst and 12g of adipic acid glutaramide, put them in a reactor heated to 250°C, keep the temperature for reaction for 3h, dry, add them to a twin-screw extruder, and after melt extrusion, place the polyethylene terephthalate in a vacuum drum drying oven, cut into slices, dry, and melt-spin to obtain polyester fiber.
[0048] S3. Preparation of silver-plated acrylic fiber
[0049] Weigh: 0.5 g of glucose, 0.4 g of potassium sodium tartrate and 10 mL of anhydrous ethanol, put them into a single-necked bottle and mix them evenly to obtain a reducing agent for later use;
[0050] Weigh: add 5% ammonia water dropwise into 20 ml of 0.15 mol / L silver nitrate solution until the solution becomes clear, add 2 mL of 20 mol / L ethylenediamine, then add 0.6 mol / L sodium hydroxide solution, adjust the solution pH to 11.1, continue to add 5% ammonia water dropwise until the reaction solution becomes clear, and obtain a silver ammonia solution for later use;
[0051] Weigh: 90 mL of ethanol and 10 mL of purified water to prepare an ethanol solution for later use;
[0052] Weigh: 10 g of acrylic fiber, 1 g of sodium carbonate and 100 mL of deionized water, place in a three-necked flask heated to 90° C., seal and keep warm for 0.5 h, wash twice with deionized water, and dry to obtain a crude acrylic fiber;
[0053] Weigh: 10 g of crude acrylic fiber, 0.5 g of mercaptopropyl triethoxysilane and 100 mL of ethanol solution in a three-necked flask, react at 40° C. for 2 h, wash twice with ethanol solution, and dry to obtain modified acrylic fiber;
[0054] Weigh: 10 g of modified acrylic fiber, 100 mL of reducing agent and 100 mL of silver ammonia solution, place in a reactor heated to 50° C., keep warm for 1 hour, wash twice with deionized water, and dry to obtain silver-plated acrylic fiber.
[0055] S4. Preparation of yeast protein adhesive
[0056] Weigh: 1.6 g of waste beer yeast powder, 20 mL of deionized water and 0.4 g of sodium hydroxide, put them in a three-necked flask heated to 100° C., add hydrochloric acid solution to adjust the pH to 9.2, and post-treat to obtain yeast protein isolate;
[0057] Weigh: 6 g of waste paper fiber, 10 g of sodium hydroxide, 100 mL of deionized water and 20 g of epichlorohydrin in a three-necked flask, react at room temperature for 4 h, wash twice with acetone and deionized water to obtain an ammoniated waste paper fiber precursor;
[0058] Weigh: add 6 g of ammoniated waste paper fiber precursor, 100 mL of N,N-dimethylformamide and 10 mL of ethylenediamine into a three-necked flask and stir, raise the temperature of the three-necked flask to 75°C, keep the temperature for 3 hours, wash the reaction solution with deionized water twice, and dry to obtain ammoniated waste paper fiber;
[0059] Weigh: 200 g of yeast protein isolate was placed in a three-necked flask, the pH was adjusted to 9.1 with sodium hydroxide solution, 3 g of ammoniated waste paper fiber and 10 g of trimethylolpropane triglycidyl ether were added, and the mixture was reacted at 40° C. for 30 min to obtain a yeast protein adhesive.
[0060] S5. Preparation of composite fibers
[0061] By jet vortex spinning, 70 parts of modified wool fiber, 10 parts of polyester fiber, 5 parts of silver-plated acrylic fiber and 15 parts of yeast protein adhesive are evenly mixed by weight to obtain a lightweight and wear-resistant composite fiber.
[0062] Example 2
[0063] This embodiment provides a method for preparing a lightweight and wear-resistant composite fiber, comprising the following steps:
[0064] S1. Preparation of modified wool fiber
[0065] Weigh: 0.2 g of catechol, 0.06 g of tea polyphenols, 0.6 mL of 50 U / mL thermophilic mycelium laccase solution, 6.6 mL of deionized water, and 1.3 mL of 0.3 mol / L sodium acetate solution, put them into a flask and mix them evenly to obtain a modified solution for later use;
[0066] Weigh: 1.5 g of wool fiber, 45 mL of deionized water and 0.45 g of sodium carbonate, put them in a three-necked flask heated to 50°C, stir for 1 hour, wash with deionized water twice, and dry to obtain alkalized wool fiber;
[0067] The dried alkalized wool fiber was placed in the inner cavity of a low-temperature plasma machine, an oxygen channel was injected, and the power was set to 150W under a pressure of 100Pa. The plasma machine continuously discharged for 5 minutes to obtain pretreated wool fiber.
[0068] Weigh: 12 g of pretreated wool fiber is immersed in 120 mL of the modification solution, kept warm for 5 hours, washed with deionized water for 3 times, and dried to obtain the modified wool fiber.
[0069] S2. Preparation of polyester fiber
[0070] Weigh: 0.2 g of ethylene glycol antimony and 2 g of triphenyl phosphite, put them into a beaker and mix them evenly to obtain a catalyst for later use;
[0071] Weigh: 13.6g of terephthalic acid, 17.9g of ethylene glycol, 0.11g of catalyst and 12.6g of adipic acid glutaramide, put them in a reactor heated to 250°C, keep the temperature for reaction for 3h, dry, add them to a twin-screw extruder, and after melt extrusion, place the polyethylene terephthalate in a vacuum drum drying oven, cut into slices, dry, and melt-spin to obtain polyester fiber.
[0072] S3. Preparation of silver-plated acrylic fiber
[0073] Weigh: 0.6 g of glucose, 0.48 g of potassium sodium tartrate and 12 mL of anhydrous ethanol, put them into a single-necked bottle and mix them evenly to obtain a reducing agent for later use;
[0074] Weigh: add 5% ammonia water dropwise into 20 ml of 0.15 mol / L silver nitrate solution until the solution becomes clear, add 3 ml of 20 mol / L ethylenediamine, then add 0.6 mol / L sodium hydroxide solution, adjust the solution pH to 11.1, continue to add 5% ammonia water dropwise until the solution becomes clear, and obtain a silver ammonia solution for later use;
[0075] Weigh: 95 mL of ethanol and 5 mL of purified water to prepare an ethanol solution for later use; weigh: 10.5 g of acrylic fiber, 1.05 g of sodium carbonate and 105 mL of deionized water, place in a three-necked flask heated to 90° C., seal and keep warm for 0.5 h, wash twice with deionized water, and dry to obtain a crude acrylic fiber product;
[0076] Weigh: 12 g of crude acrylic fiber, 0.6 g of mercaptopropyl triethoxysilane and 102 mL of ethanol solution in a three-necked flask, react at 40° C. for 2 h, wash twice with ethanol solution, and dry to obtain modified acrylic fiber;
[0077] Weigh: 10.5 g of modified acrylic fiber, 105 mL of reducing agent and 105 mL of silver ammonia solution, place in a reactor heated to 50° C., keep warm for 1 hour, wash twice with deionized water, and dry to obtain silver-plated acrylic fiber.
[0078] S4. Preparation of yeast protein adhesive
[0079] Weigh: 1.8 g of waste brewer's yeast powder, 22 mL of deionized water and 0.4 g of sodium hydroxide, put them in a three-necked flask heated to 100° C., add hydrochloric acid solution to adjust the pH to 9.2, and post-treat to obtain yeast protein isolate;
[0080] Weigh: 6.6 g of waste paper fiber, 11 g of sodium hydroxide, 110 mL of deionized water and 22 g of epichlorohydrin in a three-necked flask, react at room temperature for 4 h, wash twice with acetone and deionized water to obtain an ammoniated waste paper fiber precursor;
[0081] Weigh: add 6.6 g of ammoniated waste paper fiber precursor, 110 mL of N,N-dimethylformamide and 11 mL of ethylenediamine into a three-necked flask and stir, raise the temperature of the three-necked flask to 75° C., keep the temperature for 3 hours, wash the reaction solution with deionized water twice, and dry to obtain ammoniated waste paper fiber;
[0082] Weigh: 220 g of yeast protein isolate was placed in a three-necked flask, the pH was adjusted to 9.1 with sodium hydroxide solution, 3.3 g of ammoniated waste paper fiber and 1.1 g of trimethylolpropane triglycidyl ether were added, and the mixture was reacted at 40° C. for 30 min to obtain a yeast protein adhesive.
[0083] S5. Preparation of composite fibers
[0084] By jet vortex spinning, 72 parts of modified wool fiber, 10.5 parts of polyester fiber, 5.3 parts of silver-plated acrylic fiber and 16 parts of yeast protein adhesive are evenly mixed by weight to obtain a lightweight and wear-resistant composite fiber.
[0085] Example 3
[0086] This embodiment provides a method for preparing a lightweight and wear-resistant composite fiber, comprising the following steps:
[0087] S1. Preparation of modified wool fiber
[0088] Weigh: 0.2 g of catechol, 0.08 g of tea polyphenols, 0.8 mL of 50 U / mL thermophilic mycelium laccase solution, 8 mL of deionized water, and 1.5 mL of 0.3 mol / L sodium acetate solution, put them into a flask and mix them evenly to obtain a modified solution for later use;
[0089] Weigh: 3 g of wool fiber, 100 mL of deionized water and 0.9 g of sodium carbonate, put them in a three-necked flask heated to 50°C, stir for 1 hour, wash with deionized water twice, and dry to obtain alkalized wool fiber;
[0090] The dried alkalized wool fiber was placed in the inner cavity of a low-temperature plasma machine, an oxygen channel was injected, and the power was set to 150W under a pressure of 100Pa. The plasma machine continuously discharged for 5 minutes to obtain pretreated wool fiber.
[0091] Weigh: 25 g of pretreated wool fiber, immerse it in 250 mL of the modification solution, keep warm for 5 hours, wash it with deionized water for 3 times, and dry it to obtain the modified wool fiber.
[0092] S2. Preparation of polyester fiber
[0093] Weigh: 0.6 g of ethylene glycol antimony and 3 g of triphenyl phosphite, put them into a beaker and mix them evenly to obtain a catalyst for later use;
[0094] Weigh: 14.3g of terephthalic acid, 18.7g of ethylene glycol, 0.2g of catalyst and 13.2g of adipic acid glutaramide, put them in a reactor heated to 250°C, keep the temperature for reaction for 3h, dry, add them to a twin-screw extruder, and after melt extrusion, place the polyethylene terephthalate in a vacuum drum drying oven, cut into slices, dry, and melt-spin to obtain polyester fiber.
[0095] S3. Preparation of silver-plated acrylic fiber
[0096] Weigh: 1 g of glucose, 0.8 g of potassium sodium tartrate and 15 mL of anhydrous ethanol, put them into a single-necked bottle and mix them evenly to obtain a reducing agent for later use;
[0097] Weigh: add 6% ammonia water dropwise into 25 ml of 0.20 mol / L silver nitrate solution until the solution becomes clear, add 3 mL of 20 mol / L ethylenediamine, then add 0.7 mol / L sodium hydroxide solution, adjust the solution pH to 11.2, continue to add 6% ammonia water dropwise until the solution becomes clear, and obtain a silver ammonia solution for later use;
[0098] Weigh: 90 mL of ethanol and 10 mL of purified water to prepare an ethanol solution for later use; weigh: 15 g of acrylic fiber, 1.5 g of sodium carbonate and 150 mL of deionized water, place in a three-necked flask heated to 90° C., seal and keep warm for 0.5 h, wash twice with deionized water, and dry to obtain a crude acrylic fiber product;
[0099] Weigh: 15 g of crude acrylic fiber, 0.75 g of mercaptopropyl triethoxysilane and 150 mL of ethanol solution in a three-necked flask, react at 40° C. for 2 h, wash twice with ethanol solution, and dry to obtain modified acrylic fiber;
[0100] Weigh: 15 g of modified acrylic fiber, 150 mL of reducing agent and 150 mL of silver ammonia solution, place in a reactor heated to 50° C., keep warm for 1 hour, wash twice with deionized water, and dry to obtain silver-plated acrylic fiber.
[0101] S4. Preparation of yeast protein adhesive
[0102] Weigh: 2 g of waste brewer yeast powder, 25 mL of deionized water and 0.6 g of sodium hydroxide, put them in a three-necked flask heated to 100° C., add hydrochloric acid solution to adjust the pH to 9.2, and post-treat to obtain yeast protein isolate;
[0103] Weigh: 8 g of waste paper fiber, 13 g of sodium hydroxide, 130 mL of deionized water and 24 g of epichlorohydrin in a three-necked flask, react at room temperature for 4 h, wash twice with acetone and deionized water to obtain an ammoniated waste paper fiber precursor;
[0104] Weigh: add 8 g of ammoniated waste paper fiber precursor, 150 mL of N,N-dimethylformamide and 20 mL of ethylenediamine into a three-necked flask and stir, raise the temperature of the three-necked flask to 70°C, keep the temperature for 3 hours, wash the reaction solution with deionized water twice, and dry to obtain ammoniated waste paper fiber;
[0105] Weigh: 300 g of yeast protein isolate was placed in a three-necked flask, the pH was adjusted to 9.5 with sodium hydroxide solution, 5 g of ammoniated waste paper fiber and 16 g of trimethylolpropane triglycidyl ether were added, and the mixture was reacted at 40° C. for 30 min to obtain a yeast protein adhesive.
[0106] S5. Preparation of composite fibers
[0107] By jet vortex spinning, 75 parts of modified wool fiber, 10 parts of polyester fiber, 2 parts of silver-plated acrylic fiber and 13 parts of yeast protein adhesive are evenly mixed by weight to obtain a lightweight and wear-resistant composite fiber.
[0108] Comparative Example 1
[0109] The difference between this comparative example and Example 3 is that the steps of preparing modified wool fiber, sodium carbonate and plasma pretreatment in step S1 are omitted.
[0110] Comparative Example 2
[0111] The difference between this comparative example and Example 3 is that the step of preparing polyester fiber in step S2 is eliminated, and the polyester fiber is replaced by an equal amount of modified wool fiber in the process of preparing the composite fiber.
[0112] Comparative Example 3
[0113] The difference between this comparative example and Example 3 is that the step of preparing the silver-plated acrylic fiber in step S3 is eliminated, and the silver-plated acrylic fiber is not used in the process of preparing the composite fiber.
[0114] Comparative Example 4
[0115] The difference between this comparative example and Example 3 is that the step of preparing the yeast protein adhesive in step S4 is eliminated, and the yeast protein adhesive is not used in the process of preparing the composite fiber.
[0116] Performance Test:
[0117] The average linear density of the composite fibers prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard DB44╱T 2048-2017 "Test Method for Linear Density of Fibers";
[0118] The tensile strength and breaking strength of the composite fibers prepared in Examples 1-3 and Comparative Examples 1-3 were tested in accordance with the standard GB 1447-2005 "Test Method for Tensile Properties of Fiber Reinforced Plastics";
[0119] The resistivity of the composite fibers prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 15738-2008 "Test method for resistivity of conductive and antistatic fiber reinforced plastics";
[0120] Referring to the standard GB / T 21196.3-2007 "Determination of the abrasion resistance index of textiles by the Martindale method Part 3: Determination of mass loss", the abrasion resistance index of the composite fibers prepared in Examples 1-3 and Comparative Examples 1-3 was tested. The specific test results are shown in Table 1 - Performance test data table of each sample.
[0121] Table 1-Performance test data of each sample
[0122] Project Category Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Average linear density / tex 21.3 2.1 22.4 24.0 26.5 24.3 24.4 Elongation at break / % 29.2 37.5 34.3 32.3 28.3 28.4 21.1 Tensile strength / MPa 31.5 35.1 32.6 25.7 29.4 30.5 25.3 Resistivity / Ω·m 101 93 98 102 111 99 104 <![CDATA[Wear resistance index / times·mg -1 > 451 445 456 391 392 395 375
[0123] Data Analysis:
[0124] The data in Table 1 above are compared and analyzed. The average linear density of the wear-resistant and lightweight composite fiber prepared by the present invention is 20.1 tex, the elongation at break is 38%, the tensile strength is 34.1 MPa, the resistivity is 90 Ω·m, and the wear resistance index is 455 times·mg -1 , all data are better than the comparative example;
[0125] Data description:
[0126] In the process of preparing light and wear-resistant composite fibers, catechol and tea polyphenol oxygen oligomers catalyzed and oxidized by thermophilic mycelium laccase are prepared. The oligomers modify wool fibers to enhance the mechanical properties and wear resistance index of the wool fibers. Under weak acid conditions, catechol and tea polyphenols can form oligomers under the action of thermophilic mycelium laccase. These oligomers are physically adsorbed on the surface of the wool fibers as their concentration increases, and covalently cross-linked with the hydroxyl and amino groups of the wool fibers, thereby enhancing the elongation at break, tensile strength and wear resistance index of the composite fibers. Polyester fibers are prepared by copolymerizing adipic acid glutaramide and ethylene terephthalate. Since adipic acid glutaramide contains more methylene flexible segments, After being introduced into the main chain of ethylene terephthalate macromolecule, the macromolecular chain is more likely to move, so the polyester fiber has better softness. Polyester fiber is a synthetic fiber, and its molecular chain is mainly composed of carbon, hydrogen and oxygen, with a lower molecular weight and density, which reduces the average linear density of the further prepared composite fiber. Silver-plated acrylic fiber is obtained by silver-plating acrylic fiber treated with silane coupling agent. The acrylic fiber treated with silane coupling agent is modified with thiol, which improves the wear resistance index of the composite fiber and reduces the resistivity. The modified wool fiber, polyester fiber, silver-plated acrylic fiber and yeast protein adhesive are combined and blended to further improve the wear resistance index of the composite material and reduce its average linear density and resistivity.
[0127] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A lightweight and wear-resistant composite fiber, characterized in that: In parts by weight, the lightweight and wear-resistant composite fiber comprises: 70-75 parts of modified wool fiber, 10-12 parts of polyester fiber, 1-6 parts of silver-plated acrylic fiber and 10-18 parts of yeast protein adhesive; The method for preparing the modified wool fiber comprises the following steps: A1. Place wool fiber, deionized water and sodium carbonate in a three-necked flask heated to 40-50°C, stir for 0.5-1h, wash with deionized water 1-2 times, and dry to obtain alkalized wool fiber; A2. Place the dried alkalized wool fiber in the inner cavity of a low-temperature plasma machine, inject an oxygen channel, set the power to 100-150W at a pressure of 100-120Pa, and continue the plasma discharge treatment for 5-10min to obtain pretreated wool fiber; A3. Immerse the pretreated wool fiber in the modification solution, keep the temperature for 5-6 hours, wash with deionized water 2-3 times, and dry to obtain the modified wool fiber.
2. A lightweight and wear-resistant composite fiber according to claim 1, characterized in that: In step A1, the amount ratio of the wool fiber, deionized water and sodium carbonate solution is 1-5g:30-150mL:0.3-1g; in step A3, the amount ratio of the pretreated wool fiber and the modified liquid is 10-50g:100-300mL, and the modified liquid is composed of catechol, tea polyphenols, thermophilic mycelium laccase solution, deionized water and sodium acetate solution in a dosage ratio of 0.15-0.2g:0.05-0.1g:0.5-1mL:5-10mL:1-2mL, the concentration of the sodium acetate solution is 0.2-0.3mol / L, and the concentration of the thermophilic mycelium laccase solution is 50-60U / mL.
3. A lightweight and wear-resistant composite fiber according to claim 1, characterized in that: The preparation method of the polyester fiber is as follows: terephthalic acid, ethylene glycol, a catalyst and adipic acid glutaramide are placed in a reaction kettle heated to 230-275° C., the reaction is carried out by heat preservation for 2-5 hours, and the polyester fiber is obtained by post-processing.
4. A lightweight and wear-resistant composite fiber according to claim 3, characterized in that: The catalyst is composed of antimony glycol and triphenyl phosphite in a weight ratio of 0.1-1:1-5, and the weight ratio of terephthalic acid, ethylene glycol, catalyst and adipic acid glutaramide is 13-15:17-20:0.1-1:12-15.
5. The lightweight and wear-resistant composite fiber according to claim 1, characterized in that: The preparation method of silver-plated acrylic fiber comprises the following steps: B1. Place acrylic fiber, sodium carbonate and deionized water in a three-necked flask heated to 80-90° C., seal and keep warm for 0.5-1h, wash with deionized water 1-2 times, and dry to obtain a crude acrylic fiber product; B2, placing the crude acrylic fiber, silane coupling agent and ethanol solution in a three-necked flask, reacting at 30-40° C. for 2-3 h, washing with ethanol solution 2-3 times, and drying to obtain modified acrylic fiber; B3. Place the modified acrylic fiber, reducing agent and silver ammonia solution in a reaction kettle heated to 40-50°C, keep the temperature for reaction for 0.5-1h, wash with deionized water 1-2 times, and dry to obtain the silver-plated acrylic fiber.
6. A lightweight and wear-resistant composite fiber according to claim 5, characterized in that: In step B1, the amount ratio of the acrylic fiber, sodium carbonate and deionized water is 10-20g:1-2g:100-200mL; in step B2, the silane coupling agent is mercaptopropyl triethoxysilane, the ethanol solution is composed of ethanol and purified water in a volume ratio of 90-95:5-10, and the amount ratio of the acrylic fiber crude product, the silane coupling agent and the ethanol solution is 10-15g:0.5-2g:100-200mL; in step B3, the reducing agent is prepared from glucose, potassium sodium tartrate and anhydrous ethanol in a dosage ratio of 0.5-1g:0.4-0.8g:10-15mL, and the preparation method of the silver ammonia solution comprises: dropping 5-10% ammonia water into 20-30ml of 0.15-0.20mol / L silver nitrate solution until it is clear, adding 20-30 1-5 mL of ethylenediamine of mol / L is added, and then 0.6-0.7 mol / L of sodium hydroxide solution is added, the pH value of the reaction solution is adjusted to 11±0.2, and 5-10% ammonia water is continuously added dropwise until it becomes clear to obtain a silver ammonia solution, wherein the amount ratio of the modified acrylic fiber, the reducing solution and the silver ammonia solution is 10-15 g: 100-150 mL: 100-150 mL.
7. The lightweight and wear-resistant composite fiber according to claim 1, characterized in that: The preparation method of the yeast protein adhesive comprises the following steps: C1. Place the waste beer yeast powder, deionized water and sodium hydroxide in a three-necked flask heated to 80-100° C., add hydrochloric acid solution to adjust the pH to 9±0.5, and perform post-treatment to obtain yeast protein isolate; C2. Put waste paper fiber, sodium hydroxide, deionized water and epichlorohydrin in a three-necked flask, react at room temperature for 3-4 hours, wash with acetone and deionized water 1-2 times to obtain an ammoniated waste paper fiber precursor, add the ammoniated waste paper fiber precursor, N,N-dimethylformamide and ethylenediamine into the three-necked flask and stir, raise the temperature of the three-necked flask to 65-75° C., keep warm for 2-3 hours, and post-treat to obtain the ammoniated waste paper fiber; C3. Place yeast protein isolate in a three-necked flask, adjust pH to 9±0.2 with sodium hydroxide solution, add ammoniated waste paper fiber and trimethylolpropane triglycidyl ether, react at 40-50°C for 20-30 minutes to obtain yeast protein adhesive.
8. A lightweight and wear-resistant composite fiber according to claim 7, characterized in that: In step C1, the dosage ratio of the waste beer yeast powder, deionized water and sodium hydroxide is 1.6-2.0g:20-30mL:0.4-0.6g; in step C2, the dosage ratio of the waste paper fiber, sodium hydroxide, deionized water and epichlorohydrin is 6-8g:10-15g:100-150mL:20-30g, the dosage ratio of the ammoniated waste paper fiber precursor, N,N-dimethylformamide and ethylenediamine is 6-8g:100-150mL:10-20mL, and the post-treatment step comprises: washing the reaction solution with deionized water for 1-2 times, and drying to obtain the ammoniated waste paper fiber; in step C3, the concentration of the sodium hydroxide solution is 7.5-8.0mol / mL, and the weight ratio of the yeast protein isolate, the ammoniated waste paper fiber and trimethylolpropane triglycidyl ether is 200-400:3-6:10-20.
9. A method for preparing a lightweight and wear-resistant composite fiber suitable for use in any one of claims 1 to 8, characterized in that: The preparation method of the lightweight and wear-resistant composite fiber comprises: uniformly mixing the modified wool fiber, polyester fiber, silver-plated acrylic fiber and yeast protein adhesive by jet vortex blending to obtain the composite fiber.